2021
DOI: 10.1136/jitc-2021-003730
|View full text |Cite
|
Sign up to set email alerts
|

Leptomeningeal disease and brain control after postoperative stereotactic radiosurgery with or without immunotherapy for resected brain metastases

Abstract: PurposeImmunotherapy has shown activity in patients with brain metastases (BM) and leptomeningeal disease (LMD). We have evaluated LMD and intraparenchymal control rates for patients with resected BM receiving postoperative stereotactic radiosurgery (SRS) and immunotherapy or postoperative SRS alone. We hypothesize that postoperative SRS and immunotherapy will result in a lower rate of LMD with acceptable toxicity compared with postoperative SRS.Patients and methodsOne hundred and twenty-nine patients with non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Leptomeningeal disease was found in 7.2% of the cases in our study. This is in line with published data [ 10 , 16 , 17 ]. Nearly half of the distant brain recurrences could be salvaged with radiosurgery.…”
Section: Discussionsupporting
confidence: 93%
“…Leptomeningeal disease was found in 7.2% of the cases in our study. This is in line with published data [ 10 , 16 , 17 ]. Nearly half of the distant brain recurrences could be salvaged with radiosurgery.…”
Section: Discussionsupporting
confidence: 93%
“…Another potential pitfall of post-SRS is leptomeningeal disease (LMD), which has been reported to account for up to 35% ( 13 , 14 ). Reported risk factors for LMD include primary tumor entities of the intracranial metastasis ( 15 18 ), number of intracranial lesions ( 13 , 16 , 17 , 19 ), prior resection of an intracranial lesion ( 18 20 ), no additional immunotherapy ( 20 , 21 ) and hemorrhagic or cystic features of the lesion ( 17 ), although the results of univariate and multivariate analysis vary amongst these papers. Importantly, Foreman et al.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective studies have shown that radiotherapy cannot prolong the overall survival (OS) of LMC patients, but it can significantly alleviate symptoms and may improve drug penetration by interfering with the blood-brain barrier (BBB), thereby improving the quality of life of symptomatic disease patients [45][46][47][48].The scope of radiotherapy is determined by the degree of influence on the neural axis, with local radiotherapy being given priority. Whole brain radiation therapy (WBRT) is more commonly used for the treatment of meningeal metastases, especially in cases with brain metastases (BMs), combined with systemic drug therapy and other treatments.…”
Section: Radiotherapymentioning
confidence: 99%